A185 SUSTAINED SYMPTOM CONTROL WITH MIRIKIZUMAB IN PATIENTS WITH MODERATELY TO SEVERELY ACTIVE ULCERATIVE COLITIS IN THE LUCENT-2 MAINTENANCE TRIAL. (7th March 2023) - Dignass, A; Danese, S; Matsuoka, K; Ferrante, M; Long, M; Redondo, I; Gibble, T H; Moses, R; Li, X; Morris, N; Milch, C; Abreu, M; et al.
Abstract: Background: Mirikizumab (miri) improved symptom control in a Phase 3, multicenter, randomized, double-blind, parallel, placebo-controlled induction study at Week (W)12, in patients (pts) with moderately-to-severely active ulcerative colitis (UC; LUCENT-1). Purpose: This analysis assessed sustained symptom control during the maintenance phase through W40 (W52 of continuous therapy), among pts who were induced into clinical response with miri. Method: During the 40W maintenance study (LUCENT-2), pts (N=544) who achieved clinical response to miri 300mg Q4W by W12 of induction, were re-randomized 2:1 to subcutaneous (SC) miri 200mg (n=365) or PBO Q4W (n=179). We evaluated sustained control of stool frequency (SF), rectal bleeding (RB), bowel movement urgency (BU) and abdominal pain (AP). The proportion of pts achieving SF Remission (defined as SF=0, or SF=1 with a ≥1-point decrease from induction baseline [BL]), RB Remission (RB=0), Symptomatic Remission (both SF and RB Remission), Stable Maintenance of Symptomatic Remission (defined as pts in Symptomatic Remission for at least 7 out of 9 visits from W4 to W36 and also at Week 40 among pts in Symptomatic Remission and Clinical Response at the end of LUCENT-1), and AP Improvement (Numeric Rating Scale [NRS] pain score ≥30% improvement from BL in pts with baseline AP NRS ≥3) were assessed. BU NRS change from baseline, and the proportion of pts achieving BU Remission (NRS 0 or 1 in pts with BU NRS ≥3 at baseline) were evaluated. Result(s): A greater proportion of miri-treated pts achieved SF Remission, RB Remission and Symptomatic Remission compared to PBO at W40 (Table), with significant differences observed from W8 of LUCENT-2 (p=0.042; p=0.004; p=0.036, respectively) and maintained through W40. Miri-treated pts had a significantly higher percentage of Stable Maintenance of Symptomatic Remission (p<0.001). Pts in the miri-treatment group had a significantly greater mean reduction in BU NRS change from induction BL starting at W12 (p=0.034) onwards compared to PBO (Table). Pts assigned to miri accrued an additional 13.6 percentage-point benefit in BU Remission during the first 8W of maintenance therapy and achieved a significant greater improvement at W40 compared to PBO (p<0.001, Table). Similarly, AP was significantly improved for the miri-treated group starting at W16 (p=0.034) onwards compared to PBO. Image: Conclusion(s): Miri provides sustained control of UC symptoms including BU, RB, and SF compared to PBO in pts with moderately to severely active UC. Please acknowledge all funding agencies by checking the applicable boxes below: Other Please indicate your source of funding: Eli Lilly and Company Disclosure of Interest: A. Dignass Consultant of: AbbVie, Abivax, Amgen, Arena Pharmaceuticals, Bristol Myers Squibb (Celgene), Celltrion, Dr. Falk Pharma, Eli Lilly and Company, Ferring Pharmaceuticals, Fresenius Kabi, Galapagos, Gilead Sciences, Janssen, Merck Sharp & Dohme, Novartis, Pfizer, Pharmacosmos, Roche, Sandoz/Hexal, Takeda, Tillotts Pharma AG, and Vifor Pharma; has received lecture fees or honoraria from: AbbVie, Amgen, Bristol Myers Squibb, Dr. Falk Pharma, Ferring Pharmaceuticals, Galapagos, High5Md, Janssen, Materia, Merck Sharp & Dohme, Pfizer, Sandoz, Takeda, Tillotts Pharma AG, and Vifor Pharma, S. Danese Consultant of: AbbVie, Alimentiv, Allergan, Amgen, AstraZeneca, Athos Therapeutics, Biogen, Boehringer Ingelheim, Bristol Myers Squibb, Celgene, Celltrion, Dr. Falk Pharma, Eli Lilly and Company, Enthera, Ferring Pharmaceuticals, Gilead Sciences, Hospira, Inotrem, Janssen, Johnson & Johnson, Merck Sharp & Dohme, Mundipharma, Mylan, Pfizer, Roche, Sandoz Sublimity, Takeda, TiGenix, UCB Pharma, and Vifor Pharma, Speakers bureau of: AbbVie, Amgen, Ferring Pharmaceuticals, Gilead Sciences, Janssen, Mylan, Pfizer, and Takeda, K. Matsuoka Grant / Research support from: AbbVie, EA Pharma, JIMRO, Kissei Pharmaceutical, Kyowa Kyorin, Mitsubishi Tanabe, Mochida Pharmaceutical, and Zeria Pharmaceutical Nippon; lecture fees from: AbbVie, EA Pharma, JIMRO, Kissei Pharmaceutical, Kyowa Kyorin, Mitsubishi Tanabe, Mochida Pharmaceutical, Takeda, and Zeria Pharmaceutical Nippon, M. Ferrante Grant / Research support from: AbbVie, Amgen, Biogen, Janssen Cilag, Pfizer, Takeda, and Viatris, Consultant of: AbbVie, Boehringer Ingelheim, Celltrion, Eli Lilly and Company, Janssen Cilag, Medtronic, Merck Sharp & Dohme, Pfizer, Regeneron, Sandoz, Takeda, and Thermo Fisher Scientific, Speakers bureau of: AbbVie, Amgen, Biogen, Boehringer Ingelheim, Celltrion, Dr. Falk Pharma, Eli Lilly and Company, Ferring Pharmaceuticals, Janssen, Lamepro, Medtronic, Merck Sharp & Dohme, Mylan, Pfizer, Samsung Bioepis, Sandoz, Takeda, and Thermo Fisher Scientific, M. Long Consultant of: AbbVie, Bristol Myers Squibb, Calibr, Eli Lilly and Company, Genentech, Janssen, Pfizer, Prometheus Biosciences, Roche, Takeda, TARGET PharmaSolutions, and Theravance Biopharma, I. Redondo Employee of: Eli Lilly and Company, T. Gibble Employee of: Eli Lilly and Company, R. Moses Employee of: Eli Lilly and Company, X. Li Employee of: Eli Lilly and Company, N. Morris Employee of: Eli Lilly and Company, C. Milch Employee of: Former employee, was employed at Eli Lilly and Company at the time of study, M. Abreu Grant / Research support from: Pfizer, Prometheus Biosciences, and Takeda, Consultant of: AbbVie, Arena Pharmaceuticals, Bristol Myers Squibb, Eli Lilly and Company, Gilead Sciences, Janssen, Microba Life Sciences, Prometheus Biosciences, UCB Pharma, and WebMD, Speakers bureau of: Alimentiv, Intellisphere LLC (HCP Live Institutional Perspectives in GI), Janssen, Prime CME, and Takeda, J. Jones: None Declared